2006
DOI: 10.1091/mbc.e06-01-0053
|View full text |Cite
|
Sign up to set email alerts
|

Nonredundant Roles of Mitochondria-associated F-Box Proteins Mfb1 and Mdm30 in Maintenance of Mitochondrial Morphology in Yeast

Abstract: Mitochondria constantly fuse and divide to adapt organellar morphology to the cell’s ever-changing physiological conditions. Little is known about the molecular mechanisms regulating mitochondrial dynamics. F-box proteins are subunits of both Skp1-Cullin-F-box (SCF) ubiquitin ligases and non-SCF complexes that regulate a large number of cellular processes. Here, we analyzed the roles of two yeast F-box proteins, Mfb1 and Mdm30, in mitochondrial dynamics. Mfb1 is a novel mitochondria-associated F-box protein. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 73 publications
5
59
1
Order By: Relevance
“…The remaining 30% were partitioned between those scored as having fused, fizzed, and aggregated mitochondria (see ex-amples in Figure 1A). In agreement with previous reports (Fritz et al, 2003;Dürr et al, 2006;Escobar-Henriques et al, 2006), among mdm30⌬ cells almost 70% displayed aggregated mitochondria ( Figure 1C, vector transformation). Reintroducing MDM30 into mdm30⌬ cells (MDM30-HA), under a constitutive TEF promoter, restored mitochondrial morphology to a distribution similar to wild-type cells and completely reversed the marked increase in aggregated mitochondria seen in mdm30⌬ cells ( Figure 1C).…”
Section: The F-box Motif Of Mdm30p Is Essential For Mitochondrial Fussupporting
confidence: 93%
See 4 more Smart Citations
“…The remaining 30% were partitioned between those scored as having fused, fizzed, and aggregated mitochondria (see ex-amples in Figure 1A). In agreement with previous reports (Fritz et al, 2003;Dürr et al, 2006;Escobar-Henriques et al, 2006), among mdm30⌬ cells almost 70% displayed aggregated mitochondria ( Figure 1C, vector transformation). Reintroducing MDM30 into mdm30⌬ cells (MDM30-HA), under a constitutive TEF promoter, restored mitochondrial morphology to a distribution similar to wild-type cells and completely reversed the marked increase in aggregated mitochondria seen in mdm30⌬ cells ( Figure 1C).…”
Section: The F-box Motif Of Mdm30p Is Essential For Mitochondrial Fussupporting
confidence: 93%
“…Despite the requirement for the Mdm30p F-box in Fzo1p degradation found in Escobar-Henriques et al, the same group found that Mdm30 lacking its F-box overexpressed from the CUP promoter surprisingly restored normal mitochondrial morphology in mdm30⌬ cells (Dürr et al, 2006). In contrast, we find that, in these cells, expression of F-box mutants of Mdm30p from either the TEF or MDM30 promoter results in a failure to reverse the abnormal aggregated mitochondrial morphology seen in mdm30⌬ cells, a finding confirmed by the failure to restore growth on a nonfermentable carbon source (glycerol).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations